2003
DOI: 10.1109/jmems.2003.818455
|View full text |Cite
|
Sign up to set email alerts
|

Charge control of parallel-plate, electrostatic actuators and the tip-in instability

Abstract: Controlling the charge, rather than the voltage, on a parallel-plate, electrostatic actuator theoretically permits stable operation for all deflections. Practically, we show that, using charge control, the maximum stable deflection is limited by 1) charge pull-in, in which the actuator snaps due to the presence of parasitic capacitance and 2) tip-in, in which the rotation mode becomes unstable. This work presents a circuit that controls the amount of charge on a parallel-plate, electrostatic actuator. This cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(134 citation statements)
references
References 16 publications
4
114
0
2
Order By: Relevance
“…If we now calculate the net spring constant, it can be shown that k net = k, independent of the applied charge. This shows that applying a constant charge leads to a solution that is always stable [9][10][11]. Compared to voltage control, charge control does not result in a pull-in point, but there is also no negative spring effect.…”
Section: Actuation and Readout With Parallel-plate Capacitorsmentioning
confidence: 82%
“…If we now calculate the net spring constant, it can be shown that k net = k, independent of the applied charge. This shows that applying a constant charge leads to a solution that is always stable [9][10][11]. Compared to voltage control, charge control does not result in a pull-in point, but there is also no negative spring effect.…”
Section: Actuation and Readout With Parallel-plate Capacitorsmentioning
confidence: 82%
“…So, there is no simple formula to calculate it. People have been using lumped model (Hyun-Ho Yang et al, 2010;Seeger & Boser, 1999;Nielson & Barbastathis, 2006;Faris et al, 2006;Mol et al, 2007;Chowdhury et al, 2006;Owusu & Lewis, 2007) for decades. Lump model estimates the pull-in limit as one-third of the initial gap (d/3).…”
Section: Introductionmentioning
confidence: 99%
“…Seeger and Boser [10] presented a circuit that controls the amount of charge on a parallel-plate electrostatic actuator. They showed that charge control increased the stable ranges of motion but the maximum stable deflection is limited due to parasitic capacitance and tip-in.…”
Section: Introductionmentioning
confidence: 99%